Morphological features of the apical region in the principal cells of mongrel dog epididymis - Schimming, Bruno Cesar; Vicentini, Carlos Alberto [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2008)
The epithelial principal cells are the predominant cell type of the epididymis. These cells have been shown to be both secretory and endocytic cells. The apical region of the cytoplasm of principal cells in the mongrel dog are located close to the cell apex and tubular lumen, and shown microvilli at the luminal border and present a endocytic apparatus, that consists of coated pits and vesicles, endosomes of varying size, multivesicular bodies, and lysosomes. The endosomes, multivesicular bodies and lysosomes contained the electron-dense patches. These results suggest that principal cells of the epididymis in the dog as possess a highly developed endocytic apparatus play a role in endocytosis. These cells function are similarly to the related in other mammals, in performing endocytosis.
Keywords: Dog; Epididymis; Principal cells; Ultrastructure